Inequalities in household overcrowding in an ethnically diverse urban population: a cross-sectional study using linked health and housing records - Wilk, Marta; Harper, Gill; Liverani, Silvia; Firman, Nicola; Simon, Paul; Dezateux, Carol (International Journal of Population Data Science, 2025)
Introduction Household overcrowding is an important determinant of health and is associated with adverse child health, educational and social outcomes. Objectives We aimed to determine whether households with dependent children were more likely to be overcrowded after taking into account household ethnicity and housing tenure in an urban, ethnically diverse, and disadvantaged London population by pseudonymously linking health and property data. Methods We used pseudonymised Unique Property Reference Numbers to link electronic health records to Energy Performance Certificate property data in north-east London and identified 332,473 households comprising 1,093,047 people. Our primary outcomes were overcrowding measures based on a bedroom standard and a space standard (space per person; m2). We examined household level associations of overcrowding with presence of children in the household before and after adjusting for household ethnicity and tenure. We used multivariable logistic regression to estimate the adjusted odds (aOR) and 95% Confidence Intervals (CI) of bedroom standard overcrowding and linear regression to estimate effects (95% CI) on space per person. Results Overall, 42.8% (142,401/332,473) of households included children, 54.5% were of White household ethnicity, and 58.4% in private or social rented accommodation. 22.5% (32,075/142,401) and 45.9% (65,388/142,401) of households with children were overcrowded by the bedroom and space standards respectively compared with 4.7% (8,953/190,072) and 9.6% (18,229/190,072) without children. After adjusting for household ethnicity and housing tenure, households with children were more likely to be overcrowded (aOR [95% CI] 5.54 [5.40-5.68] and had 22.61m2 (95%CI: -22.75,-22.46) less space per person than those without children. Conclusions Up-to-date estimates of household overcrowding measured by bedroom and space standards can be derived from linked housing and health records. Our findings highlight the inequalities in overcrowding experienced by households with children and enable future work using linked data to evaluate impacts of overcrowding on children's health.